Simultaneous radical cystectomy and nephroureterectomy in the treatment of panurothelial carcinoma: a systematic review and single-arm meta-analysis - Liu, Yang; Zhang, Huimin; Wen, Zhi; Jiang, Yu; Huang, Jing; Wang, Chongjian; Chen, Caixia; Wang, Jiahao; Bao, Erhao; Yang, Xuesong (Frontiers in Oncology, 2023)
Background Panurothelial carcinoma is a rare and aggressive malignancy that requires effective treatment strategies to enhance patient outcomes. Methods We conducted a systematic search of English publications in databases including PubMed, Embase, Cochrane Library, and Web of Science up to May 2023. The quality of the literature was assessed using the Newcastle-Ottawa Scale (NOS) and the Methodological Quality and Synthesis of Case Series and Case Reports tool. Data statistics and analysis were performed using Stata 15.1 software (StataSE, USA). Results Six studies involving 339 patients were included in the analysis. Meta-analysis revealed that Simultaneous Radical Cystectomy and Nephroureterectomy had 2-year and 5-year overall survival rates of 68% (95% CI 60%-76%, I2 = 12.4%, P < 0.001) and 44% (95% CI 36%-53%, I2 = 0, P < 0.001), respectively. The 2-year and 5-year progression-free survival rates were 91% (95% CI 86%-95%, I2 = 95%, P < 0.001) and 65% (95% CI 58%-73%, I2 = 91.5%, P < 0.001), respectively. The 2-year and 5-year cancer-specific survival rates were 73% (95% CI 66%-81%, I2 = 16.7%, P < 0.001) and 57% (95% CI 49%-66%, I2 = 0, P < 0.001), respectively. Additionally, the incidence of minor complications was 19% (95% CI 15%-23%, P < 0.01), major complications was 49% (95% CI 34%-63%, P < 0.01), and the intraoperative blood transfusion rate was 53% (95% CI 44%-61%, P < 0.01). Conclusions Simultaneous radical cystectomy and nephroureterectomy represent feasible approaches for the treatment of Panurothelial carcinoma. Nonetheless, a comprehensive assessment of the surgical risks and benefits is imperative, and larger-scale prospective cohort studies are required to validate therapeutic efficacy. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42023426401.